Pengaruh Multinasionality, Tax Haven, Thin Capitalization, dan Firm Size terhadap Tax Avoidance - Zanra, Sri Wahyuni; Zubir, Zubir (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This research aims to test and analyze the influence of multinationality, tax havens, thin capitalization, and frame size on tax avoidance. This research uses a quantitative method. The population in this study includes manufacturing sector companies listed on the IDX from 2019 to the end of 2021, with a total sample of 53 companies that meet the established criteria. Data analysis techniques used descriptive statistical tests and multiple regression tests with the Statistical Package for Social Science (SPSS). The implications of this research are expected to minimize the occurrence of tax avoidance to support state revenues. Based on the results of the analysis, it shows that multinationality, thin capitalization, and firm size have a significant effect on the effective tax rate, whereas tax havens do not have a significant effect on the effective tax rate.Keywords: Multinasionality, Tax Haven, Thin Capitalization, Firm Size, Effective Tax Rate